Higher Education Investment in the Arab States of the Gulf : Strategies for Excellence and Diversity. - Eickelman, Dale (Gulf studies., 2016)
Over the last half-century, the GCC states have invested on a huge scale in higher education, but the stated commitment to internationally recognized excellence has also to come to terms with tradition._x000B_ These pressure points are examined here in a number of comparative studies, and cover among other topics: higher education as soft power to promote regional or global influence, intense reliance on foreign instructors, citizen entitlements, badu and hadar divisions, gender separation, different visions of language of instruction, marginalization of foreign students and faculty outside.